2006
DOI: 10.1111/j.1525-142x.2006.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of Bmp2a, Bmp2b, and Bmp4 expression patterns within and between dentitions of teleost fishes

Abstract: The diversity of tooth location in teleost fishes provides an excellent system for comparing genetic divergence between teeth in different species (phylogenetic homologs) with divergence between teeth within one species (iterative homologs). We have chosen to examine the expression of three members of the bone morphogenetic protein (Bmp) family because they are known to play multiple roles in tooth development and evolution in tetrapod vertebrates. We characterized expression of Bmp2a, Bmp2b, and Bmp4 during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 76 publications
6
71
0
Order By: Relevance
“…Wise and Stock (14) found that loss of oral bmp2b expression is associated with cypriniform oral tooth loss. Dlx2 expression is known to be regulated by Bmp4 in mouse tooth development (15), but whether dental Dlx2b expression in teleosts is regulated by Bmp2b remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wise and Stock (14) found that loss of oral bmp2b expression is associated with cypriniform oral tooth loss. Dlx2 expression is known to be regulated by Bmp4 in mouse tooth development (15), but whether dental Dlx2b expression in teleosts is regulated by Bmp2b remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that failure to regain oral teeth is not the result of an absence of selection for their function. The specific genetic changes that caused loss of cypriniform oral teeth remain unknown (14,19). If our finding that Dlx2b retains the capacity for expression in oral teeth is representative of the genetic pathways controlling tooth development, it is possible that the redeployment or modification of one or a few upstream signals could restore oral teeth.…”
Section: The Cypriniform Oral Dlx2b Enhancer Has Been Preserved For >50mentioning
confidence: 96%
See 1 more Smart Citation
“…3 A and E) and a variety of tooth germ markers (Fig. S4) that have been shown to differ in their expression between wild-type zebrafish and A. mexicanus (21,32). We therefore asked whether the oral epithelium is competent to respond to Eda.…”
Section: Eda Overexpression Does Not Restore Teeth To the Mouth Of Thmentioning
confidence: 99%
“…Probes for A. mexicanus bmp2a, bmp2b, dlx2b, pitx2, and shh were as previously described (21,32). A. mexicanus edar and edaradd probes correspond to the positions listed for their zebrafish orthologs, and the eda and fgf4 probes for this species comprised the regions corresponding to zebrafish positions 769-1151 (NM_001115064) and 538-887 (NM_131635.2), respectively.…”
Section: Construction Of Transgenic Zebrafish Lines Overexpressing Edamentioning
confidence: 99%